2020
DOI: 10.1007/s10236-020-01383-3
|View full text |Cite
|
Sign up to set email alerts
|

Tidal response to sea level rise and bathymetric changes in the German Wadden Sea

Abstract: Tidally dominated coasts are directly affected not only by projected rise in mean sea level, but also by changes in tidal dynamics due to sea level rise and bathymetric changes. By use of a hydrodynamic model, which covers the entire German Bight (South-Eastern North Sea), we analyse the effects of sea level rise and potential bathymetric changes in the Wadden Sea on tidal current velocities. The model results indicate that tidal current velocities in the tidal inlets and channels of the Wadden Sea are increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Regarding the future morphological evolution of intertidal areas in the Wadden Sea, the availability of sediments from internal and external sources has to be considered. Tidal inlets, channels, and ebb-tidal deltas act as internal sediment sources in a tidal basin, while external sediments may be provided by foreshore areas, barrier islands, or remote sites (Wachler et al, 2020). Existing empirical (Hofstede, 2002) and schematized models (Van Goor et al, 2003) have shown that SLR may cause an internal sediment redistribution from tidal inlets, channels, and ebb-tidal deltas to the intertidal flats.…”
Section: Scenario Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the future morphological evolution of intertidal areas in the Wadden Sea, the availability of sediments from internal and external sources has to be considered. Tidal inlets, channels, and ebb-tidal deltas act as internal sediment sources in a tidal basin, while external sediments may be provided by foreshore areas, barrier islands, or remote sites (Wachler et al, 2020). Existing empirical (Hofstede, 2002) and schematized models (Van Goor et al, 2003) have shown that SLR may cause an internal sediment redistribution from tidal inlets, channels, and ebb-tidal deltas to the intertidal flats.…”
Section: Scenario Developmentmentioning
confidence: 99%
“…We assumed that sediments from external sources are fully accountable for the vertical accretion in the intertidal flats of the Wadden Sea for simplicity. In contrast to Wachler et al (2020), a deepening of local tidal inlets and channels was neglected in our model. Furthermore, we uniformly applied each considered rate of vertical accretion to the entire intertidal flats of the Wadden Sea.…”
Section: Scenario Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The sediment budget analysis performed by Benninghoff and Winter (2019) for the period between 1998 and 2016 showed that the tidal flats in this region accumulate sediments at a rate higher than the observed mean rate of SLR, which ranges from 2.2 to 6.6 mm/yr for the German Bight (Wahl et al, 2013). Indeed, the SLR scenario of Wachler et al (2020) demonstrated that elevated tidal flats and deepened tidal channels tend to counteract the pure effects of SLR on tidal current velocities. In the following, we will refer to the change in the local depth as a function of time as a "bathymetric change.…”
Section: Introductionmentioning
confidence: 96%